2019
DOI: 10.3389/fncel.2019.00443
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Connectivity Amongst Interneuronal Components of the Locomotor CPG

Abstract: The basic rhythmic activity characteristic of locomotion in mammals is generated by a neural network, located in the spinal cord, known as the locomotor central pattern generator (CPG). Although a great deal of effort has gone into the study of this neural circuit over the past century, identification and characterization of its component interneurons has proven to be challenging, largely due to their location and distribution. Recent work incorporating a molecular approach has provided a great deal of insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Thus, students and teachers have a similar ability to control the cycle stability of rhythmic movement, and compared with spatial stability, consistent performance in temporal stability with experts can be achieved in a relatively short period of training. Many studies have explored the control mechanisms of vertebrate rhythmic movement and revealed that rhythmic activities are produced from the central pattern generators (CPGs) in the spine [31,32]. The CPGs not only produce rhythms but also alter their frequencies and patterns; unlike spatial and (c, d) showed the operation stability of lifting-thrusting skill and twisting skill, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, students and teachers have a similar ability to control the cycle stability of rhythmic movement, and compared with spatial stability, consistent performance in temporal stability with experts can be achieved in a relatively short period of training. Many studies have explored the control mechanisms of vertebrate rhythmic movement and revealed that rhythmic activities are produced from the central pattern generators (CPGs) in the spine [31,32]. The CPGs not only produce rhythms but also alter their frequencies and patterns; unlike spatial and (c, d) showed the operation stability of lifting-thrusting skill and twisting skill, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of genetically defined interneuron populations has enabled us to characterize their specific functions in locomotor behaviors (Goulding, 2009; Gosgnach et al, 2017; Deska-Gauthier and Zhang, 2019). Until now, however, most experimental data were obtained by genetically eliminating certain classes of spinal interneurons without clear understanding of connectivity among the spinal interneurons (Lanuza et al, 2004; Gosgnach et al, 2006; Crone et al, 2008; Zhang et al, 2008; Talpalar et al, 2013; Bellardita and Kiehn, 2015; Haque and Gosgnach, 2019). In the case of V3 interneurons, genetic deletion of entire V3 population reduced the general robustness of the rhythmicity of the in vivo and in vitro locomotor activity and led to unstable gaits (Zhang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This is true in models that include nominal categories of interneurons (Grillner et al 2007), models that include identified categories of interneurons (Danner et al 2017, and models that dispense with directed structure altogether (Lindén et al 2022). Despite the clear functional significance, there are very few methodical analyses of connectivity among interneuron classes (Haque & Gosgnach 2019). An integrated map of interneuron connectivity will not only reveal areas that need investigation but also steer new avenues of inquiry into assembly of spinal networks, interaction of different functional modules, and comparisons across species.…”
Section: Interconnectivity In the Ventral Spinal Cordmentioning
confidence: 99%